Using Classification Based Approach on Online Social Media as a Marketing Channel for Building and Improving Consumer Perception of Brands: An Empirical Analysis of Facebook Users in Pakistan - Meer Wali Ur Rehman Khan (Journal of Peace, Development and Communication, 2022)
The aim of the research is to inspect and examine the use of Facebook as a marketing channel and tool for building and improving overall perception of the consumers about the brands. Brand managers and research scholars are continuously trying to comprehend the effects of the use of social media as a marketing channel and tool on consumer perception of brands, however there are still loopholes exist when it comes to the question as how consumer perceive brands?. This research focuses on the optimal techniques and ways of using social media i.e. Facebook use as a marketing tool in order to build and improve online brand equity. In order to collect data, online survey through questionnaire was conducted by targeting the active users of Facebook in Pakistan. After analyzing the data through Statistical tools i.e. SPSS v.21 and AMOS v.22, the results showed that there is a strong and positive impact of Facebook on brand awareness and brand image. The results further conclude that brand awareness is essential to construct and build brand image. Moreover, the research provides a clear solution and understanding of the various marketing activities performed on Facebook like searching information, quality and performance of e-service and engagement and involvement of brands and its impact on knowledge of brand (brand awareness & brand image) which then lead to brand equity by using the Keller model. Additionally, research demonstrates that in order to create customer brand relationships on social networking sites like Facebook, it is important to comprehend both media system reliance i.e. GOALS and uses and gratifications i.e. NEEDS, that is a classification based approach on social media users, which in turn produced positive results.